Global Shocks and their Impacton Low-Income Countries : Lessons From theglobal Financial Crisis - Papageorgiou, Chris (IMF Working Papers; Working Paper ;, 2011)
This paper investigates the short-run effects of the 2007-09 global financial crisis on growth in (mainly non-fuel exporting) low-income countries (LICs). Four conclusions stand out. First, for many individual LICs, 2009 was not extraordinarily calamitous; however, aggregate LIC output declined sharply because LICs were unusually synchronized. Second, the growth declines are on average well explained by the decline in export demand. Third, if the external environment facing LICs improves as forecast, their growth should rebound sharply. Finally, and contrary to received wisdom, there are few robust relationships between the cross-country growth variation and the policy and structural environment; the main exceptions are reserve coverage and labor-market flexibility.